Advances in polymeric materials for dental applications. Issue 5 (15th December 2016) - Xu, Xinyuan; He, Libang; Zhu, Bengao; Li, Jiyao; Li, Jianshu
Abstract : This review focuses on the relationship between the structures and properties of various polymers for different applications in dentistry. Abstract : Over the past decade, polymeric materials for clinical dental applications have been developed with excellent properties and various functionalities. This review outlines the present understanding and design of polymeric dental materials based on structure–property–function relationships. First, the chemistry/microstructure of polymeric materials will be reviewed. Then, the resultant properties such as mechanical, thermal, visco-elastic, and water solution properties, as well as additional bio-functionalities such as antibacterial capabilities, remineralization, and bioactive-delivery properties, will be reviewed for specific dental applications. Finally, perspectives and challenges regarding the rational design and application of polymeric dental materials will be discussed.